A Sociological Study of the Interrelationship between Education and Society with Special Reference to Social Institutions - Dr. Santosh Kumar Singh (Knowledgeable Research A Multidisciplinary Journal, 2025)
The present study examines the role of education within the broader context of social institutions, positioning it at the centre of sociological discourse. The study adopts a purely descriptive approach and conceptualizes education not merely as a process of acquiring knowledge or skills, but as a significant social institution. It highlights education as a powerful medium for socialization, value formation, cultural transmission, and social change. The present study undertakes a comprehensive examination of the interrelations between education and key social institutions, including the family, religion, politics, the economy, and the media. It posits that education not only evolves in response to the structural and functional demands of society but also actively shapes the trajectory of social mobility, direction of change, and the broader future of the social order. The discourse highlights that the relationship between education and society is both mutual and dynamic. While education serves to preserve social traditions and cultural values, it also fosters social consciousness and propels society toward progressive transformation. In this manner, education becomes a foundational medium for coordinating various social institutions, thereby guiding the processes of social cohesion, development, and sustainable change.